Efforts to Improve Work Performance Through Work Placement, Motivation And Non-Physical Work Environment (Case Study at Budisatrya Foundation) - Srie Hartati; Rafida Khairan; Manda Dwipayani Bhastary; Emilia Embun Sari (Publisher Cv. Inara, 2020)
The success of an organization is inseparable from the quality of human resources that the organization has. Work achievement deserves a look in support of the achievement of organization goals. The main focus in this study is to analyze the effect of work placement, motivation and non-physical work environment on teacher work performance at Budisatrya Foundation. Data collection using questionnaires. The results of the study showed that all variables of work placement, motivation and non-physical work environment significantly affected the teacher's work performance. The variable that has the greatest influence in improving work performance is the non-physical work environment. The implications of the findings suggest that the variables of work placement, motivation and non-physical work environment that exist at Foundation Budisatrya have been excellent. Especially the emotional connection between the teacher and the foundation.